(untitled) (Research, Society and Development, 2025)
Pulpal calcification is generally defined as partial or total obliteration of the pulp cavity by mineralized tissue, often associated with physiological aspects and the patient’s dental history. This condition leads to alterations in tooth anatomy that may hinder the performance of endodontic treatment, since such cases do not allow the adoption of conventional protocols. The present study aimed to identify, in an observational, cross-sectional, and retrospective manner, the main difficulties associated with the diagnosis and treatment of teeth with calcified canals. For this purpose, dental records, digital radiographs, and, when available, cone beam computed tomography scans related to endodontic treatments performed by the same endodontist over a 10-year period (May 2014 to May 2024) were analyzed. Data were collected at the private clinic EndoMais, located in Uberlândia, Minas Gerais, Brazil. A total of 54 teeth were evaluated, showing a higher prevalence of calcified elements in women between 40 and 69 years of age. It was observed that single-rooted teeth exhibited calcifications distributed along all three root thirds, whereas bi-rooted molars showed a greater tendency toward apical calcification. The main clinical difficulties were related to coronal access, canal location, and debridement, challenges mitigated by the use of an operating microscope, ultrasound, and cone beam computed tomography. Working length determination proved more accurate when complemented with electronic apex locators and radiographs. Obturation, even in altered anatomies, achieved satisfactory results using the thermoplasticized technique, reinforcing the importance of combining technological resources in the management of calcified canals.